Exploring Pre-Service Early Childhood Education (ECE) Teachers' Experience with Nutrition Education - Resor, Jessica (East Carolina University, 2018)
This study aimed to understand early childhood pre-service teachers' thoughts and experiences with nutrition education in their undergraduate program and how these experiences play into their perceptions and future use of nutrition education within their own classrooms. Using phenomenology, eleven in-depth telephonic interviews were conducted with early childhood pre-service teachers from two public universities in the state of North Carolina. All participants were females. Eight participants were White/Caucasian and the remaining three participants were Black/African American. Their ages ranged between 21-46 years (mean age 29 years). Six participants were enrolled in a face-to-face licensure degree-seeking program, while five participants completed their licensure degree program through online education. Only two participants were Licensure Only/Licensure Add-On students, who already had a bachelor's degree in a different or related field to education, and were seeking a Birth through Kindergarten license. Six participants planned to include nutrition related activities during student-teaching. Four emergent themes were familial and life experiences, academic experiences, food choices and mealtime, and strategies. Implications for teacher education programs and the early childhood education field are discussed.
Keywords: pre-service; phenomenology; Early childhood teachers--North Carolina--Attitudes; Early childhood teachers--Training of--North Carolina; Women teachers--North Carolina--Attitudes; Nutrition policy--North Carolina; Health promotion--North Carolina--Planning